PENERAPAN PERMAINAN ESTAFET KATA UNTUK MENINGKATKAN HASIL BELAJAR LARI PADA SISWA KELAS IV SD N 2 CIPAKU KEC. KERTANEGARA KAB. PURBALINGGA (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this research is to improve learning outcomes run on fourth grade students of SD Negeri 2 Cipaku.This study uses a classroom action research. This study consisted of two cycles, each cycle lasts for one learning sessions. Each cycle consists of four steps: planning, implementation, observation and reflection. The subjects were fourth grade students of SD Negeri 2 Cipaku amounting to 24 students with a composition of 13 female students and 11 male students. Data collection techniques used are observation, questionnaires and documentation. The data analysis used is quantitative description. Results of the classroom action research can be concluded, in the first cycle of learning outcomes completeness percentage of 75% to 75% details psychomotor aspects, affective aspects of 70.83%, 37.5%, and cognitive aspects of the average value obtained was 79.78 and the number of students who completed is 18 students. In the second cycle completeness percentage increased to 87.5% with the details of psychomotor aspects of 95.83%, 79.17% affective aspects, cognitive aspects of 91.67% and the average value obtained was 85.62 and the number of students who pass are 21 students..